Elementary Students’ Mathematical Literacy in Solving Realistic Mathematics through Math Trail Activities - Arif Rahman Hakim; Kartono Kartono; Wardono Wardono; Adi Nur Cahyono (Universitas Negeri Semarang, 2022)
Mathematical literacy is defined as the ability to formulate, use and interpret mathematics in a variety of contexts, including systematic reasoning, using mathematical concepts, procedures, facts, and tools to describe, explain, and predict phenomena to help individuals. One of the things that underlie the low ranking of Indonesian students is weak mathematical literacy is the lack of use of non-routine problems that are made based on real-life contexts, so they can only work on routine questions. This study was conducted to explore mathematical literacy indicators that appear in solving real problems through math trail activities. The research subjects were taken from the ranking of students in the previous class, so that 1 male student, namely S1, and 1 female student, namely S2, were selected, who ranked highest in the class for each gender. S1 shows indicators of mathematical literacy in the form of communication, mathematization, reasoning, and argumentation, designing a strategy, using symbolic, formal, technical language and operation, and using mathematical tools. While S2 is in communication, mathematization, reasoning and argumentation, designing a strategy, representation, formal, technical language and operation, and using mathematical tools.